Physical Geography - Physical Geography (Taylor & Francis, 2026)
Physical Geography publishes original research on physical processes that shape the physical landscape and are critical to human-environment interactions. Papers focusing on the integration of climatology, geomorphology, hydrology, biogeography, and soils and their impact on human-environment interactions are particularly encouraged.
FI 0.32
Q4
Keywords: Biological; Earth & Environmental Food Science; Acuerdos transformativos; Transformative agreements; Geografía física; Geomorfología; Climatología; Hidrología; Procesos ambientales